EFEKTIVITAS PEMELIHARAAN TUNAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI - Andika Prawanto; Kiky Nurfitri Sari; Indriati Meilina Sari; Ela Hasri Windari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
As the main commodity in the market, the demand for chili continues to increase. Meanwhile, its average productivity is only 9.01 tons/ha nationally and classified as low. The main cause of this low productivity is the infeasibility of chili cultivation techniques among farmers. The optimal cultivation technique is expected to increase the rate of chili productivity, for example through pruning the buds of chili plants. Therefore, this study aimed to determine the best number of buds to perform an optimal growth and yield of chili plants. The experimental design used in this study was a completely randomized design (CRD) where the buds treatment as followed: T0 (without maintaining bud), T1 (maintaining 1 bud), T2 (maintaining 2 buds), and T3 (maintaining 3 buds). Those treatments were executed with 3 repetitions. The observation data were analyzed using ANOVA at the 5% significance level. The results showed that the bud's maintenance on chili plants did not affect the variables of plant height, dichotomous branch height, canopy width, fruit weight per plant, number of fruits per plant, and weight per fruit.